Woman, Mother, Wet Nurse: Engine of Child Health Promotion in the Spanish Monarchy (1850–1910) - Siles-González, José (Int J Environ Res Public Health, 2020)
In Spain, the wet nurse increased the survival of children through care and breastfeeding of other women’s children. They had a great development together with the Spanish monarchy between 1850 and 1910. The aim is to identify the role of wet nurses in the Spanish monarchy and the survival of the royal infants (s. XIX–XX). A scoping review is presented to study documents about the wet nurse in the Spanish monarchy. Applying the dialectical structural model of care (DSMC). Recognizing five thematic blocks that shape the historical-cultural model. Books, decrees and databases were analyzed: Scopus, Scielo, Dialnet, Cuiden, Medline/Pubmed, CINAHL, Science Direct and Google Scholar, from January to July 2020. The selection process was rigorous because it was difficult to choose. They had to overcome medical and moral exams. The selected rural northern wet nurses emigrated to Madrid. The contract was regulated by laws and paid. Wet nurses were hired by the monarchy due to health problems of the biological mother and a need for greater offspring. The wet nurse wore a typical costume, a symbol of wealth. The northern wet nurses hired by the monarchists have been the engine that has promoted the health of infants through the breastfeeding process.